Lincoln: Part Two - Donald, David Herbert, 1920-2009; Dietz, Norman; Recoded Books, LLC. (Prince Frederick, MD : Recorded Books, 2014)
Donald spent 50 years studying Lincoln tracing his rise from humble origins to the pinnacle of the presidency. He reveals the development of the future President's character and shows how Lincoln's enormous capacity for growth enabled one of the least experienced men ever elected to high office to become a giant in the annals of American politics. And he depicts a man who was basically passive by nature, yet ambitious enough to take enormous risks and overcome repeated defeats.
IN PROCESS RECORD.
Compact disc.
Title from container.
In container (17 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Keywords: Lincoln, Abraham, -- 1809-1865; Presidents -- United States -- Biography; Audiobooks